TP53-dependence on the effect of doxorubicin and Src inhibitor combination therapy - Yun Sun Lee; Ji-Yoon Choi; Jeeyun Lee; Da Mi Shim; Jaesoo Kim; Woong-Yang Park; Do-Hyun Nam; Sung Wook Seo (Tumor Biology)
The anticancer effects of Src kinase inhibitors are controversial. This study found an association between alterations in the TP53 gene and the synergy score for combination treatment with doxorubicin and an Src kinase inhibitor using human osteosarcoma cell lines (MG63 and U2OS) and human colon cancer cell line. Doxorubicin was found to activate signal transducer and activator of transcription 3 via Src kinase in cancer cells harboring alterations in TP53. A drug combination study using patient-derived cells confirmed that an Src kinase inhibitor synergizes with doxorubicin in cancer cells harboring alterations in TP53, while antagonizing its effect in cancer cells expressing wild-type TP53. Our findings suggest that genetic alterations in TP53 are a critical factor in determining the use of a combination treatment of doxorubicin and Src inhibitors.